2017
DOI: 10.1038/s41598-017-18389-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq reveals seven promising candidate genes affecting the proportion of thick egg albumen in layer-type chickens

Abstract: Eggs with a much higher proportion of thick albumen are preferred in the layer industry, as they are favoured by consumers. However, the genetic factors affecting the thick egg albumen trait have not been elucidated. Using RNA sequencing, we explored the magnum transcriptome in 9 Rhode Island white layers: four layers with phenotypes of extremely high ratios of thick to thin albumen (high thick albumen, HTA) and five with extremely low ratios (low thick albumen, LTA). A total of 220 genes were differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…A r t i c l e physiological or production stages [8]. Regarding eggshell quality, previous studies have focused primarily on transcriptomic analysis in the uterus, which can reveal the molecular mechanisms that may cause laying hens with different eggshell quality [9,10]. For the eggshell color, Wang et al [11] conducted transcriptomic analysis to identify molecular factors affecting blue coloration in the uterus of duck with blue-green eggshells and reported a large difference in cholesterol biosynthesis and ion levels involved in the modulation of the transporting activity of bile pigment transporters.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…A r t i c l e physiological or production stages [8]. Regarding eggshell quality, previous studies have focused primarily on transcriptomic analysis in the uterus, which can reveal the molecular mechanisms that may cause laying hens with different eggshell quality [9,10]. For the eggshell color, Wang et al [11] conducted transcriptomic analysis to identify molecular factors affecting blue coloration in the uterus of duck with blue-green eggshells and reported a large difference in cholesterol biosynthesis and ion levels involved in the modulation of the transporting activity of bile pigment transporters.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Message RNA was extracted from the total RNA and cut into short fragments with~200 bases as templates for cDNA synthesis. The cDNAs subsequently used to establish a cDNA library by PCR amplification and sequenced by using an Illumina HiSeqTM 2500 platform [31]. Clean reads were obtained by trimming the adaptor sequences from raw reads, and these reads were then were used for further transcript annotation and calculation bases on the fragments per kilobase per million reads (FPKM) method.…”
Section: Rna Sequencing (Rna-seq) and Data Analysismentioning
confidence: 99%
“…Differential gene expressions (DEGs) were identified with the DESeq software package. The Benjamini-Hochberg false discovery rate was employed to correct the p values with a significant level set at 0.05 [31].…”
Section: Rna Sequencing (Rna-seq) and Data Analysismentioning
confidence: 99%
“…More recently, RNA sequencing (RNA-seq) has become a powerful method for precise quantification of not only coding but also non-coding RNAs. With recent improvements of chicken genome information, RNA-seq successfully revealed the intriguing genes affecting egg albumen in layers 9 and comb size of cocks 10 . The latest studies using RNA-seq have also reported differential gene expression profiles in breast muscles of modern and foundation broiler lines 11,12 or those in broiler lines with high- and low-ultimate pH 13 .…”
Section: Introductionmentioning
confidence: 99%